PENYELESAIAN KASUS KEKERASAN SEKSUAL TERHADAP WANITA DI WILAYAH SHAN MYANMAR DARI PERSPEKTIF KONVENSI INTERNASIONAL TENTANG PENGHAPUSAN SEGALA BENTUK DISKRIMINASI TERHADAP PEREMPUAN (CONVENTION ON THE ELIMINATION OF ALL FORMS OF DISCRIMINATION AGAINST WOM - Sukmartini, Putu; Tuni Cakabawa Landra, Putu; Eka Wisanjaya, I Gede Pasek (Kertha Negara : Journal Ilmu Hukum; Vol. 03, No. 01, Februari 2015)
There have been a number of cases of sexual violence in Shan region of Myanmar causedby the expansion of the anti-insurgency by the Myanmar military regime in some ethnicminority areas. Sexual violences on women and children were used as punishment forresistance against the ethnic groups that performed the military regime of Myanmar. It iscertainly ironic because Myanmar is a country that ratified Convention on the Eliminationof All Forms of Discrimination Against Women (CEDAW). This paper is a normative legalresearch that discusses the CEDAW mechanism in resolving cases of sexual violence in theShan region of Myanmar. This paper also discusses the obstacles that arise in theresolution of the case in concern.
Keywords: CEDAW, Sexual Violence, Military Regime, Shan